Land use planning and property development: Factors affecting urban housing development in Kuala Lumpur, Malaysia - Ahmad, Faizah; Mohd, Ibrahim; Wan Abd Aziz, Wan Nor Azriyati (2009)
Various literatures on land use planning unveil diverse negative effects on property development, particularly on urban housing supply. The effects can be categorized into location, quantity, intensity and production costs which then lead to an increasing mismatch between housing supply and demand. The Malaysian planning system has partly contributed to housing problems in urban areas. The purpose of this paper is to examine planning factors affecting urban housing development in the capital city of Kuala Lumpur within the established institutional framework. The study encompasses planning approval process, legislative provisions and planning decisions. Primary data were gathered through questionnaire surveys to private housing developers and in-depth interviews with local planning authority. The findings demonstrate the influence of planning decisions over implementation of land use planning policies.